CMOS-Compatible and Low-Cost Thin Film MACE Approach for Light-Emitting Si NWs Fabrication - Antonio Alessio Leonardi; Maria José Lo Faro; Alessia Irrera (Nanomaterials, 2020)
Silicon nanowires (Si NWs) are emerging as an innovative building block in several fields, such as microelectronics, energetics, photonics, and sensing. The interest in Si NWs is related to the high surface to volume ratio and the simpler coupling with the industrial flat architecture. In particular, Si NWs emerge as a very promising material to couple the light to silicon. However, with the standard synthesis methods, the realization of quantum-confined Si NWs is very complex and often requires expensive equipment. Metal-Assisted Chemical Etching (MACE) is gaining more and more attention as a novel approach able to guarantee high-quality Si NWs and high density with a cost-effective approach. Our group has recently modified the traditional MACE approach through the use of thin metal films, obtaining a strong control on the optical and structural properties of the Si NWs as a function of the etching process. This method is Complementary Metal-Oxide-Semiconductors (CMOS)-technology compatible, low-cost, and permits us to obtain a high density, and room temperature light-emitting Si NWs due to the quantum confinement effect. A strong control on the Si NWs characteristics may pave the way to a real industrial transfer of this fabrication methodology for both microelectronics and optoelectronics applications.